Uma solução computacional para geração automática de peças com flexibilidade de processo para simulação - Gonçalves Filho, Eduardo Vila; Gorgulho Júnior, José Hamilton Chaves (Revista Gestão da Produção Operações e Sistemas, 2006)
This paper presents the methodology developed to automatically generate a large set of parts with a variancein the number of operations and also with process flexibility. Initially, the text presents the characteristics of aturbulent manufacturing environment and the physical arrangements proposed to be performed in thissituation. Following that, the distributed arrangement is highlighted and the problem to be analyzed bysimulation is presented. The following item is about the process flexibility. After the presentation of themethodology, the results obtained by computational implementation are shown. At the end, the comments onthe obtained results are presented.Keywords: Simulation; Process flexibility; Layout.